Understanding Mathematics Teachers' Perspectives on Deep Learning Oriented to Students' Computational Abilities - Khoerul Umam; Ishaq Nuriadin; Ervin Azhar; Hari Setiadi (Universitas Islam Sultan Agung, 2025)
Good and quality mathematics learning is influenced by mathematics teachers' beliefs about appropriate learning strategies and methods. This study aims to determine the extent to which mathematics teachers prepare, develop, and adapt deep learning in mathematics classrooms. Mathematics teachers were the subjects of this study because the foundation of the strength of mathematics learning in its implementation is highly dependent on their perceptions. Data collection was conducted face-to-face and online, combining in-depth interviews and closed-group discussions. The data were analyzed using thematic analysis, combining themes and categories formed during the analysis process. The results indicate the relevance of deep learning in the context of mathematics learning, the diverse readiness of mathematics teachers in implementing deep learning, and the need for training required by teachers to support the creation of higher-quality learning. The impact of this research will provide input to the government in implementing the program, the need for regular evaluation and structured and massive training so that implementation can be carried out more evenly throughout Indonesia